EFFECTIVENESS OF CONTEXTUAL LEARNING PROBLEM BASED TEACHING MODEL IN INCREASING ACHIEVEMENTS AND STRENGTHENING SCIENCE MATERIALS IN VB MIN 1 PALU CITY STUDENTS - Andayani Andayani (Jurnal Dikdas, 2020)
To be able to learn something well, we need to listen, see, ask questions about it, and discuss it with others. It's not just that, students need to "do it", that is, describe things in their own way, show examples, try to practice skills and do assignments that demand the knowledge they have gained.This research uses action research as much as three rounds. Each round consists of four stages, namely: design, activities and observations, reflection, and refissions. The target of this research is the students of class VB MIN 1 Palu City. The data obtained in the form of formative test results, observation sheets of teaching and learning activities.From the results of analysts it was found that student achievement increased from cycle I to cycle III namely, cycle I (64.00%), cycle II (76.00%), cycle III (88.00%).The conclusion of this study is that problem-based contextual learning can positively influence the learning motivation of VB MIN 1 Palu students, and this learning model can be used as an alternative to learning science.